Typing of poultry Salmonella enteritidis and Salmonella typhimurium isolates by pulsed-field gel electrophoresis. - Lim, Yu Qian. (2010)
Salmonella enterica subsp. enterica (S.) has been the most common pathogen causing gastroenteritidis in humans for many years. Infections by Salmonella are more often acquired by consumption of contaminated sources, especially poultry and eggs. With its ability to infect a broad host range, Salmonella will continue to post a threat to public health.